“Poor Effort” Does Not Account for Reduced Forced Vital Capacity in Asthmatic Children - Feng, Yong; Yang, Que; Shang, Yunxiao (Frontiers in Pediatrics, 2021)
Purpose: Poor forced vital capacity (FVC) effort has been considered to be the main reason for FVC reduction by the ATS/ERS guideline, however this has rarely been mentioned in previous studies. The present study aims to determine whether reduced FVC in asthmatic children is correlated to poor FVC effort. Methods: A total of 209 asthmatic children within 5-13 years old were included and divided into reduced FVC (“Restricted”, n=66) and typical obstruction group (“Obstructed”, n=143). Forced expiratory flows before and after bronchodilation were recorded in asthmatic children. The differences in clinical characteristics, spirometric results, FVC effort and bronchodilator response were compared between two groups. Exhalation time (ET) was divided into effective ET (ETe) and plateau ET (ETp) by the start point of exhalation plateau on the time-volume curve. FVC effort was assessed by ET, ETp and back extrapolated volume (EV)/FVC (%). Results: Asthmatic children in the “Restricted” group had significantly higher slow vital capacity (SVC)/FVC (%), higher EV/FVC (%), shorter ET, shorter ETe and longer ETp, when compared to those with “Obstructed”. In the “Obstructed” group, ET (r=0.201, P=0.016) and ETe (r=0.496, P<0.001) positively correlated with FVC, and ETp (r=-0.224, P=0.007) negatively correlated with FVC. In the “Restricted” group, FVC positively correlated with ETe (r=0.350, P=0.004), but not ET and ETp. FVC z-score significantly correlated with total IgE (n=51, r=-0.349, P=0.012) and with FEF25-75% z-score (n=66, r=0.531, P<0.001) in the “Restricted” group. The further logistic regression revealed that the risk of “Restricted” increased by 1.12 (95% CI: 1.04-1.22, P=0.005) with every 1% increase in %ΔFVC. In subjects with “Restricted” and bronchodilation tests, %ΔFVC was significantly associated with FeNO (n=29, r=0.386, P=0.039), FEF25-75% z-score (n=29, r=-0.472, P=0.010), and SVC/FVC (%) (n=19, r=0.477, P=0.039), but not with EV/FVC (%), ET, ETe or ETp (P>0.05). Conclusion: These findings suggested that “poor FVC effort” does not account for the FVC reduction in asthmatic children. Short ET and high SVC/FVC (%)are characteristics of reduced FVC.